2010
DOI: 10.1093/annonc/mdq078
|View full text |Cite
|
Sign up to set email alerts
|

Survival of patients with multiple primary malignancies: a study of 783 patients with gastrointestinal stromal tumor

Abstract: Approximately 20% of patients with GIST develop other cancers. Inferior median 5-year survival was observed in patients with GIST with two or more other cancers. The etiology and clinical implications of other malignancies in patients with GIST should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 16 publications
9
83
3
2
Order By: Relevance
“…By contrast, prior cancer diagnosis was generally associated with improved clinical outcomes, regardless of timing in relation to the lung cancer diagnosis. Similar trends have been identified in lymphoma and gastrointestinal malignancy populations (46)(47)(48). There are many potential explanations for these trends.…”
Section: Articlesupporting
confidence: 81%
“…By contrast, prior cancer diagnosis was generally associated with improved clinical outcomes, regardless of timing in relation to the lung cancer diagnosis. Similar trends have been identified in lymphoma and gastrointestinal malignancy populations (46)(47)(48). There are many potential explanations for these trends.…”
Section: Articlesupporting
confidence: 81%
“…The synchronous occurrence of GIST and other primary gastrointestinal malignancies has been reported previously (3)(4)(5)(6)(7)(8)(9)(10). However, the synchronous existence of lung cancer and GIST seems to be extremely rare (7)(8)(9)(10). We experienced a case of advanced stage lung adenocarcinoma associated with intestinal GIST.…”
Section: Introductionmentioning
confidence: 63%
“…Synchronous and asynchronous cases of GIST and other malignancies have been studied in several series (3)(4)(5)(6)(7)(8)(9). Based on these reports, GIST associated with other primary malignancies occurs at incidence rates ranging from 2.9% to 32.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Although the lesions described in the literature primarily involved the gastrointestinal tract, breast, and skin (non-melanoma), other sites can also be affected. Pandurengan et al (8) described a case of gastrointestinal stromal tumor associated with gastric lymphoma, while Troyanova et al (9) described an increased risk of MPT in Bulgarian patients diagnosed with malignant non-melanoma of the skin, primarily affecting the head and neck, thyroid, lung, larynx, bladder, colon, melanoma, and non-Hodgkin lymphoma. Dasanu et al (2) reported a case of pancreatic adenocarcinoma associated with mantle cell lymphoma; this was the only case we found in PubMed and Bireme describing MPT involving the specific subtype of mantle cell lymphoma, similar to the present case.…”
Section: Discussionmentioning
confidence: 99%